Mini Grids for Timely and Low-Cost Electrification in Ghana : Exploring Regulatory and Business Models for Electrifying the Lake Volta Region - Energy Sector Management Assistance Program (Washington, DC: World Bank, 2017)
Ghana has been remarkably successful in extending its national grid into the rural areas. According to its Ministry of Power, about 83.4 percent of communities with more than 500 people have access to grid electricity. The main remaining frontier is to bring electricity to communities living on islands in Lake Volta and in isolated lakeside locations. The summary of this report first highlights some areas where clear recommendations have emerged, and then presents areas where choices are to be made between options with different advantages and disadvantages. The purpose of this assignment is to explore the most feasible business models for mini and micro grids for Ghana’s island and lake-side communities, together with a pragmatic policy and regulatory regime that will reinforce the development of such systems. The remainder of the report is arranged as follows: 1) Chapter 1 does the Analysis and discussion of the various options for business models of mini grids; (ii) Chapter 2 is about Analysis and discussion of the costs of mini grid delivery, tariff calculations and financing options; (iii) Chapter 3 discusses on the Review and proposals for required policy, legislation, regulations, permits, and institutional arrangements; and (iv) Chapter 4 concludes with Review and recommendations for necessary technical assistance to implement the delivery of mini grids.